EXAMINATION OF CARTOON FILMS REFLECTING THE LIFE OF THE NEIGHBORHOOD - SABANCI POLAT, Elif (SSD Journal, 2023)
Although each person is an individual with a different personality trait, they must act in unity. We need to live in solidarity with the consciousness of unity. While the consciousness of our children is pure, let's fulfill the duties of raising them with correct information instead of false information. Everyone involved in the educational process in the development of children needs to act consciously. We should live in a social unity, not apart from our family, neighbors, neighbourhoods, provinces, and country. Within the scope of this research, it is discussed how the neighborhood consciousness is reached in the cartoons that our children watch to spend time. How much space is given to the neighborhood consciousness, where the consciousness of social unity is widespread. How the neighborhood consciousness, where individuals live together and social relations are strong, is handled in cartoons. The cartoons broadcasted in TRTÇOCUK, our national cartoon channel, were examined. Among these cartoons, Pırıl, Aslan and Rafadan Tayfa cartoons, which were seen in accordance with the scope of the research, were selected. It has been examined how the social life in the union in the neighborhood is reflected.